2017
DOI: 10.1038/s41467-017-02024-y
|View full text |Cite
|
Sign up to set email alerts
|

Oscillatory brain activity in spontaneous and induced sleep stages in flies

Abstract: Sleep is a dynamic process comprising multiple stages, each associated with distinct electrophysiological properties and potentially serving different functions. While these phenomena are well described in vertebrates, it is unclear if invertebrates have distinct sleep stages. We perform local field potential (LFP) recordings on flies spontaneously sleeping, and compare their brain activity to flies induced to sleep using either genetic activation of sleep-promoting circuitry or the GABAA agonist Gaboxadol. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
130
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(170 citation statements)
references
References 61 publications
(116 reference statements)
22
130
1
Order By: Relevance
“…Such an increase has not been reported for insects (van Swinderen, 2006; Kirszenblat and van Swinderen, 2015), and we did not observe this here (the results did not change with longer time window (18 s) and/or using a unipolar reference scheme [data not shown]). Interestingly, a recent study reported that sleep induction in flies is accompanied by an increase in 7–10 Hz LFPs power (Yap et al, 2017). However, this was not observed for pharmacologically induced sleep, so any relevance to general anesthesia remains unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such an increase has not been reported for insects (van Swinderen, 2006; Kirszenblat and van Swinderen, 2015), and we did not observe this here (the results did not change with longer time window (18 s) and/or using a unipolar reference scheme [data not shown]). Interestingly, a recent study reported that sleep induction in flies is accompanied by an increase in 7–10 Hz LFPs power (Yap et al, 2017). However, this was not observed for pharmacologically induced sleep, so any relevance to general anesthesia remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that the fly heartbeat can manifest as low-frequency (2–4 Hz) oscillatory activity in central channels (Paulk et al, 2013b; Yap et al, 2017). Heartbeats are unlikely to affect the results presented here because we use bipolar rereferencing which eliminates common input to neighboring channels, as may be expected from a muscle artifact (Cohen and Tsuchiya, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…However, in invertebrates it is unknown whether neural oscillations can gate specific behaviors, and whether an electrophysiological sleep correlate, such as slowwave oscillations, exists or is involved in sleep regulation. Local field potential (LFP) measurements in the Drosophila brain indicate that the frequency of large scale compound neuronal activity is reduced during sleep [8][9][10] opening up the possibility that, comparable to vertebrates, slow oscillatory activity could be involved in mediating sleep. Yet, such oscillations so far have not been identified and it remains unknown, which and how neural networks would generate slow-wave oscillations that could be crucial for sleep regulation.…”
Section: Introductionmentioning
confidence: 99%
“…Although there is nothing known about the neuronal mechanism underlying these oscillations nor their purpose (if any), recent work in flies reported increased 7-10 Hz oscillations within the central brain during spontaneous sleep. Although this is much more rapid than mammalian delta waves (Yap et al, 2017), it is tempting to connect these oscillations as well as those we have observed to mammalian sleep. Moreover, it will be interesting to test whether APDN firing can produce similar oscillations or local field potential changes in other sleep-relevant central brain regions like dFSB.…”
Section: The Induction Of Potent Eb Ring Neuron Calcium Oscillations mentioning
confidence: 52%
“…Sleep in diverse systems is characterized by a set of common features. They include reduced locomotor activity, increased arousal threshold and altered neuronal oscillation patterns in higher brain centers (Yap et al, 2017). Although there is no single mechanism that can account for all these features, we present here a novel anatomical circuit in the fly brain that influences all of them.…”
Section: Discussionmentioning
confidence: 95%